Radiopacity performances of precipitated ZrO2-doped Bi2O3 powders and the influences of dopant concentrations and sintering temperatures. Issue 16 (November 2017) - Chen, May-Show; Yang, Jen-Chang; Lai, Fu-Chih; Chen, Chin-Yi; Hsieh, Ming-Yang; Fang, Alex; Chen, Shih-Hsun; Lin, Chung-Kwei
Abstract: In this study, Bi2 O3 powders were modified into ZrO2 -doped Bi2 O3 powders by adding zirconium oxide through precipitation processes. The radiopacity and physical properties of as-synthesized and heat-treated products were investigated. The products were primarily composed of a mixture of β -Bi7.38 Zr0.62 O12.31 and α -Bi2 O3 obtained below 700 °C, then transferred to β -Bi7.38 Zr0.62 O12.31 phase above 750 °C. With regard to zirconia dopant concentration effects, more zirconium oxide precipitated onto the Bi2 O3 surface as the x values of Bi2−x Zrx O3+x/2 increased from 0.2 to 1.0. As the x value of Bi2−x Zrx O3+x/2 powder increased, so too did the surface roughness as a result of zirconia precipitation. In terms of temperature effect, increasing heating temperatures resulted in a smoother powder surface due to liquid phase sintering effect. As for radiopacity analysis, the performances were significantly improved by heat treatments and the effects generally enhanced with increasing temperatures. The overall maximum radiopacity value measured after an 800 °C heat treatment was 5.57±0.28 mm Al for precipitated ZrO2 -doped Bi2 O3 powders at x=0.2.